2004
DOI: 10.1038/sj.gt.3302272
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a recombinant Sendai virus that is selectively activated and lyses human tumor cells expressing matrix metalloproteinases

Abstract: Malignant tumor cells often express matrix metalloproteinases (MMPs) at a high level to enable their dissemination and metastasis. Sendai virus (SeV), a nonsegmented negative strand RNA virus, spreads in the target tissues in vivo via cleavage activation of the viral fusion glycoprotein by a tissue-specific, trypsin-like enzyme. By deleting the viral matrix protein, we previously generated a recombinant SeV that does not bud to mature virions, but is highly fusogenic and spreads extensively from cell to cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 43 publications
1
44
0
1
Order By: Relevance
“…We examined three deleting mutants (Fct27, Fct14, Fct4), as shown in Figure 1a, and the fusion efficiency was quantified by counting the nuclei per formed syncytium. 8 As shown in Figure 1b, syncytia formation was observed only in cells with cotransfection of paired membrane glycoproteins (F and HN). The highest ratio of fusion activity, six times higher than that seen by wildtype F gene cotransfected (Po0.01), was seen in the use of a truncated clone (Fct14); therefore, we concluded that Fct14 should be used in our new design of an oncolytic SeV.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…We examined three deleting mutants (Fct27, Fct14, Fct4), as shown in Figure 1a, and the fusion efficiency was quantified by counting the nuclei per formed syncytium. 8 As shown in Figure 1b, syncytia formation was observed only in cells with cotransfection of paired membrane glycoproteins (F and HN). The highest ratio of fusion activity, six times higher than that seen by wildtype F gene cotransfected (Po0.01), was seen in the use of a truncated clone (Fct14); therefore, we concluded that Fct14 should be used in our new design of an oncolytic SeV.…”
Section: Resultsmentioning
confidence: 80%
“…8 As expected, this new class of SeV vectors spread widely from cell to cell through fusion of the plasma membranes, forming syncytia among the MMPexpressing tumor cells in vitro, and led the tumor to extensive death in vivo, without releasing secondary vector particles. 8 Our subsequent studies examining the utility of the vector among various human cancer cell lines from different origins, however, showed that the efficacy of this prototype vector was relatively limited because of (1) the requirement for a relatively high expression level of MMPs for efficient cell death and (2) the limited numbers of MMP-expressing tumor cells, less than 20% (unpublished observation).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations